Partisipasi Politik Buruh Migran Indonesia di Malaysia pada Pemilu 2009 dan 2014 - Suryani, Suryani; Azmi, Ana Sabhana (Jurnal Review Politik, 2017)
This article tried to analyze the political participation of Indonesian Migrant Workers in Malaysia in the election of 2009 and 2014. The implementation of political rights of Indonesian migrant workers still becomea homework for Indonesian government. The freedom and democratization should be the main point for political activities in Indonesia. Besides, the contribution of migrant workers has to be considered, especially those who work in Malaysia. The implementation of political participation needs a good political education that has to be owned by migrant workers. By using political participation theory, state theory in policy and protection theory, also the concept of political education, this research done in qualitative, deep interview as the collecting data method. After being depth analyzed, this research found that the increasing of political participation of Indonesian migrant workers in Malaysia on the election 2014 compared with 2009, is much more because figure factor. The figure is considered as a great and humble political actor, and believed can accommodate the interest of migrant workers. The political education of Indonesian migrant workers in Malaysia is really needed, in term of increasing the number of political participation of migrant. Not only migrant workers, political education also needed by election organizers.